The Impact of the Global Economic Crisis on the Performance of Industries and Firms in Poland. Does Internationalisation Matter? - Gorynia, Marian; Jankowska, Barbara; Mroczek-Dąbrowska, Katarzyna; Trąpczyński, Piotr; Dzikowska, Marlena (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The global economic crisis has significantly altered the landscape of contemporary business markets worldwide. This article aims to verify how severely the economic crisis affected Polish industries and changed the competitive position of Polish companies. The authors put forward a research proposition which states that companies open to foreign cooperation (both exports and imports) were more likely to suffer from economic disturbances than companies that were domestically focused. The outcomes of the study are twofold. First, 24 manufacturing industries were ranked to check which of them suffered the most and the least as the result of the economic crisis. Secondly, using the CATI method 701 companies operating in the above‑mentioned industries were surveyed. The analysis details how the competitive position of these companies was shaped depending on their degree of internationalisation. The obtained results were afterwards compared with a previously conducted literature review, and the article attempts to present the impact of the global economic crisis on both industries (mesoeconomic perspective) and individual companies (microeconomic perspective).